Fatores condicionantes dos casos de sífilis congênita, entre 2007 e 2017, no município de Guarapuava - PR - Massuqueto, Raphaella Rosa Horst (2018)
The congenital syphilis is the result of the Treponema pallidum hematogenous dissemination in the infected pregnant woman for its concept in a transplacental way. This situation can be avoided from an adequate early treatment and diagnosis. However, the epidemiological situation of congenital syphilis in Brazil has been a big challenge to control, despite of the protocols that it must be a disease with an obligation in its notification. This study describes the epidemiological characteristics in the congenital syphilis notified cases in relation to the conditional factors to the health in Guarapuava-PR, between the years of 2007 and 2017. It is an epidemiological descriptive study from the analysis of notified data in the SINAN registers and in the electronic medical records. In the proposal period were identified 28 notification of congenital syphilis in the county in which 19 had as a final diagnosis the recent congenital syphilis, 8 were discarded and 1 stillborn. We described a growing through the years, with an increase in the notification of congenital syphilis from 2013 (incidence of 1,71 cases per 1000 borned alive) and 2017 (incidence in 2 cases per 1000 borned alive). The pregnant woman profiles its similar to the results described in the literature, with a predominance of the diseases in young adults (half between age of 14 and 20) with low schooling level (92,8% just high school) and were housewives. The majority has not made the prenatal yet, what brings difficulty in the disease diagnosis, and neither the pregnant woman nor her partner made the treatment. It can infer that the determine factors of congenital syphilis concentrate not only in the quality of the prenatal, but is a cultural, social and economics fact, where the pregnant women live.